Correlation Between Platelet Count and Hematocrit Value in Hospitalized Patients with Dengue Hemorrhagic Fever at RSUD Dokter Pirngadi Medan, 2022-2023 - Damayanti Saragih; Bastanta Tarigan; Novrina Situmorang; Maestro Simanjuntak; Batara Simangunsong (Jurnal Kedokteran Methodist, 2025)
Background : Dengue Hemorrhagic Fever (DHF) is an infectious diseasecaused by the dengue virus transmitted through the bite of the Aedesaegypti mosquito. This disease remains a global health issue, including inIndonesia. One of the main complications of DHF is thrombocytopeniaand hemoconcentration, which can lead to serious conditions such ashypovolemic shock. Objective: The objective of this study is to determinethe correlation between platelet count and hematocrit levels in DHFpatients at Dr. Pirngadi General Hospital, Medan City, in 2022-2023.Research Method: This research is observational with a cross-sectionaldesign. The sampling technique used is purposive sampling. The data usedin this study are secondary data obtained from medical records, involvingthe collection of information from existing patient medical records at Dr.Pirngadi General Hospital, Medan. Data presentation includes univariateand bivariate analysis using the Spearman correlation test. Results: Theresults of this study, with a total of 280 samples, show a significantnegative correlation between platelet count and hematocrit levels in DHFpatients, both in males (rs calculated (0.619) > rs table (0.350); 0.05) andfemales (rs calculated (0.296) > rs table (0.169); 0.05). Conclusion:There is a significant negative correlation between platelet count andhematocrit levels in DHF patients hospitalized at Dr. Pirngadi GeneralHospital, Medan City